Social Entrepreneurship Model Counseling on Sharia Cooperatives Managers and Members - Muhardi, M; ., Nurdin; Gandana Madjakusumah, D.; Irfani, Aminuddin (KnE Social Sciences, 2023)
Mungsolkanas Mosque is one of the mosques that has a Sharia cooperative that operates as a community empowerment unit. However, the resulting empowerment cooperatives are not optimal. It is indicated that this mosque is still finding it difficult to optimize its empowerment effort to improve society’s quality of life. This community service activity is intended to provide solutions needed by cooperative managers and managers so that the resulting empowerment benefits are more optimal. It is also expected that through this activity, the empowerment effort can be further enhanced by actively involving the society in economic activity development. The method used in this community service activity is knowledge improvement through FGD. After conducting preliminary research, we discovered that the less optimal output of empowerment is caused by: (a) a lack of knowledge of managers about the activities of the entrepreneurial concept; and (b) the difficulty of cooperative managers in identifying the potential of the community in order to determine the type of entrepreneurial activity to be developed. After this activity, we concluded that there is a significant knowledge improvement from the participants, by increased knowledge on how to determine the most suitable business line to enhance the cooperative’s contribution on sovereignty improvement in society. Keywords: social entrepreneurship, mosque cooperatives, society empowerment